Evaluating The Most Reliable Combination Of Non-Destructive Test Methods For Concrete Uniformity And Relative Compressive Strength. - Sibisi, Nokwanda Pearl (Department of Civil Engineering, 2024)
The ever increasing rate of deterioration of concrete structures due to poor construction techniques and quality control has resulted in an increasing demand for non-destructive testing to ascertain the compressive strength and quality of concrete, at both the construction stage and during the service life of concrete structures. This is because destructive testing approaches such as core drilling are mainly representative of the areas in the concrete where they have been extracted, while NDT testing can be conducted in as many areas on the concrete in order to obtain a true characterisation of the properties of concrete without causing any destruction to a concrete structure. The non-destructive testing approach is also preferred due to its efficiency in terms of time and cost. Therefore, the accuracy of non-destructive test results for estimating the compressive strength and quality of concrete is imperative and has also been a subject of significant scrutiny. Previous research revealed that numerous factors in the concrete can largely affect the accuracy of NDT results obtained from each type of NDT test method. Hence, a more accurate approach exists in combining test results from different NDT methods to improve their reliability to estimate the compressive strength, quality and uniformity of concrete. The aim of this study was to evaluate reliable combinations of NDT methods for the estimation of the compressive strength and uniformity of concrete. This was achieved through non-destructive testing of two reinforced concrete beams using the Rebound hammer method, Ultrasonic pulse velocity and Impact Echo methods before coring and 28 days after coring and repair of the two beams. Destructive testing was also conducted through drilling of cores from the RC beams and laboratory testing for compressive strength, for a comparative analysis between results obtained through non-destructive testing and those obtained through destructive testing, as well as for calibration purposes. It was found that both the combinations of the Rebound hammer and UPV and the Rebound Hammer and Impact Echo methods are both reliable for estimating the strength of concrete, both results had a closer correlation to the known compressive strength compared to individual methods, before and after calibration. The estimated compressive strength test results after coring and repair of beams showed the negative impact caused by the non-uniformity of concrete properties on the accuracy of the estimated compressive strength using NDT results. The applicability of the Rebound Hammer, UPV and Impact Echo to assess the quality and uniformity of concrete was also ascertained